Self-control and emotion regulation as mediators of the mindfulness-aggression association - Wong, Rui Yee (Nanyang Technological University, 2020)
Studies show that aggression affects both individuals and societies negatively. To combat these negative effects, some studies have started investigating the effect of mindfulness on aggression. However, most studies focus on physical aggression. As there exists a wide range of expressions of aggression, this study aims to fill the gap in the current literature by investigating the effect of mindfulness on physical aggression, verbal aggression, anger, hostility, and cyber-aggression, giving a more holistic view of aggression, as well as to investigate the cross-cultural validity of the current literature. In addition, there has been little research conducted to elucidate the pathways of the effect of mindfulness on aggression. Currently, the general theory of crime, the frustration-aggression hypothesis, and the cognitive-neoassociation theory of aggression suggest that some possible factors that affect aggression include self-control and emotion regulation. Thus, this study investigated if self-control and emotion regulation mediated the mindfulness-aggression association. A series of questionnaires were administered to participants, measuring trait mindfulness, aggression, self-control, and emotional regulation. Regression and mediation models were conducted for these key measures. Results show that, in an Asian undergraduate sample, there is an association between trait mindfulness and physical aggression, verbal aggression, anger, hostility, and cyber-aggression. Results also indicated that self-control was a significant mediator of the mindfulness-aggression association, while emotion regulation was a nonsignificant mediator of the mindfulness-aggression association. Mindfulness interventions focusing on self-control may thus be of use in targeting perpetrators of aggression. Keywords: mindfulness; aggression; cyber-aggression; self-control; emotion regulation